Laparoscopic repeat hepatectomy versus conventional open repeat hepatectomy for recurrent hepatocellular carcinoma: A systematic review and meta-analysis - Hao, Fulong; Li, Hancong; Li, Nan; Li, Jiaxin; Wu, Hong (Frontiers in Oncology, 2022)
BACKGROUND: Repeat hepatectomy has been proven to be an effective treatment in patients with recurrent hepatocellular carcinoma (RHCC). However, for RHCC, it is still controversial whether laparoscopic hepatectomy is superior to conventional ones. The present meta-analysis was carried out to investigate the safety and overall effect of laparoscopic repeat hepatectomy (LRH) to open repeat hepatectomy (ORH) for patients with RHCC. METHODS: A meta-analysis was registered at PROSPERO and the registration number is CRD42021257569. PubMed, Web of Science, and EMBASE were searched based on a defined search strategy to identify eligible studies before April 25, 2022. Data on operative times, bleeding volume, overall complications, mortality, blood transfusion, length of stay, overall survival rate, and long-term recurrence-free survival rate were subjected to meta-analysis. RESULTS: Overall, we identified 9 studies of LRH versus ORH enrolling a total of 945 patients (460 and 485 underwent LRH and ORH, respectively). The present meta-analysis revealed non-significant differences in operative time, blood transfusion, overall complications, mortality, overall survival rate, and long-term recurrence-free survival rate between the two groups. Alternatively, compared LRH with ORH, LRH has less bleeding volume (p＜0.001) and a shorter length of stay (p=0.005). CONCLUSION: LRH is a feasible and effective treatment strategy for RHCC.